2015
DOI: 10.1039/c5tb00096c
|View full text |Cite
|
Sign up to set email alerts
|

Integrated 3D conducting polymer-based bioelectronics for capture and release of circulating tumor cells

Abstract: 3D conducting polymer-based bioelectronic interface (BEI) devices for dynamically controlling circulating tumor cell capture/release performance through the cyclic potential of electrical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 41 publications
0
50
1
Order By: Relevance
“…The rapid developing cell printing and organs printing technology enables the production of complex biomimetic structures directly from computer-aided design models [114][115][116][117]. These techniques might eventually offer the opportunity for manufacturing bio-artificial organs to create functional substitutes for treating organs failure or dysfunctionality.…”
Section: Biochemical Analysis On 3d Printed Lab-on-a-chip Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid developing cell printing and organs printing technology enables the production of complex biomimetic structures directly from computer-aided design models [114][115][116][117]. These techniques might eventually offer the opportunity for manufacturing bio-artificial organs to create functional substitutes for treating organs failure or dysfunctionality.…”
Section: Biochemical Analysis On 3d Printed Lab-on-a-chip Devicesmentioning
confidence: 99%
“…To obtain formidable and low-cost clinical therapeutic intervention platforms employed to monitor tumor progression and metathesis, fast rare cell isolation for circulating tumor cells (CTCs) genotyping to confirm the character of CTCs in tumor liquid biopsy was fairly significant. Hsiao et al created attractive bioelectronic interfaces (BEIs) based on conducting polymer with 3D structure [116]. Such structure could be incorporated on electronic devices for rare CTCs isolation, detection, and collection by means of an electrically caused cell release from chips with transfer printing technology.…”
Section: Cell Culture and Separationmentioning
confidence: 99%
“…The key concept for the capture and release of the CTCs was the dynamic control of the Pll-g-PEG-biotin coating on the PEDOTAc nanorods. The function of the device was demonstrated by capturing of human breast adenocarcinoma cells, which subsequently could be released by repeated potential sweeping between -0.8 to 0.5 V [144].…”
Section: Cell Biologymentioning
confidence: 99%
“…We have previously shown that a variety of nanotopographies of varying size and morphology can be engineered using PEDOT by simply changing the electropolymerization voltage or temperature . These scientific developments have led to applications of PEDOT‐materials for cancer therapeutics . A vast majority of studies conducted to understand the cancer cell behavior employ inorganic materials.…”
Section: Introductionmentioning
confidence: 99%